Influence of weather, dryspells and management practices on aflatoxin contamination in groundnut - A. SUBRAMANYAM and D. BALAGURAVAIAH, T. YELLAMANDA REDDY, B.N. SULOCHANAMMA, (Indian Phytopathology, 2003)
Contamination of groundnut with aflatoxins, is a serious problem that deteriorates quality. The adoption of improved production technologies is likely to help in improving the productivity and quality of groundnut by reducing aflatoxin contamination. Among 189 samples analysed, aflatoxin could not be assayed in 10.2 % samples and very high level of aflatoxin was observed in 9.7% of samples ranging from 35 to 8172.3 mg kg'1. In TMV-2, the widely grown variety recorded> 30 mg kg'1 of aflatoxin contamination in 16.3%samples while samples of other varieties viz., JL-24, TAG-24, TG-26 and GG-2 had aflatoxin at very low level Â« 5 mg kg'1).Rainfed groundnut was more contaminated with aflatoxin ranging from 0-8172.3mg kg'1than winter crop under irrigated condition (0-535.3mg kg'1).Due to adoption of improved practices 90.2% of the samples had less than 15 mg kg'\ while in control plots only 75.7% of the samples had less than 15 mg kg'1aflatoxin. Improved management practices had reduced aflatoxin load in kharif than in rabi.